Possible hydrogeological and thermal conditions of the Quilmes Tectonic Trough (Buenos Aires Province, Argentina): a working hypothesis - Eduardo A. Rossello; Gerardo Veroslavsky; Jorge N. Santa Cruz (Boletín Geológico, 2021)
The proposal of the Quilmes Tectonic Trough (Fosa tectónica de Quilmes – FQ) as the extension of the southern end of the Santa Lucía basin in Uruguay and its connection to the Salado basin in Argentina suggest the existence of a large sedimentary volume capable of housing a new aquifer on the La Plata River coast. However, the sedimentary volumes that form the FQ are hidden under a thick, recently deposited cover, and thus, there is a lack of studies on the nature of this formation. Nevertheless, the Uruguayan section of the Meso-Cenozoic depocenter of the Santa Lucía basin has been more thoroughly studied for hydrocarbon exploration, which enabled us to estimate the equivalent tectosedimentary characteristics in the FQ. In the Uruguayan territory, three aquifer systems of the Santa Lucía basin are exploited: the Raigón (Plio-Pleistocene) aquifer, which is the most important source of groundwater for various uses in the south-central region of Uruguay, and the Mercedes (Upper Cretaceous) and Migues (Lower Cretaceous) aquifers, which are also used, albeit to a lesser extent, for drinking water, irrigation, and industrial purposes. The Migues aquifer, the least known of the three, shows a variable depth ranging from 100 to 1500 m and considerable stratigraphic sequences of porous and permeable sandstones. These sandstones provide the aquifer with very good qualities as a reservoir rock; as such, the Migues aquifer has been studied for its potential natural gas reserves and geothermal and water resources. Accordingly, if the same sequences with equivalent sedimentary and hydrogeological qualities are present in the FQ, similar aquifers with interesting properties may remain unidentified along the Buenos Aires coast beneath the intensely explored Puelches, Pampeano and Paraná aquifers. In conclusion, specific exploratory activities may prove the existence and quality of these hydrogeological resources, the regional slope toward the southwest from the Uruguayan outcrops, upwelling or semiupwelling conditions and even geothermal energy associated with the deepest cretaceous aquifers.